Participation in job-related training in European countries: the impact of skill supply and demand characteristics. Issue 5 (4th July 2017) - Saar, Ellu; Räis, Mari Liis
Abstract: Ageing populations and accelerating economic change make it increasingly important to update the skill levels of populations over the whole life course. Adult education is believed to allow adults' skills to adapt continuously to constantly changing economic requirements. Both research into adult education, and discussions on lifelong learning policies have been dominated by a supply side view of the labour market (the human capital approach), which has tended to underplay the role of the demand side of the labour market. This paper aims to extend previous analyses by examining how both labour supply and demand characteristics influence participation in non-formal job-related education in countries with different skill formation systems. The paper emphasises skill use at work. The purpose is to understand better the relationship between participation in adult education and workers' skills profiles as well as the extent to which those skills are used in jobs and how this relationship differs in different countries. We used data from the Programme for the International Assessment of Adult Competencies and applied logistic regression analysis.